Effect of contralateral acoustic stimulation on cochlear tuning measured using stimulus frequency and distortion product OAEs. - Boothalingam, Sriram; Lineton, Ben (International Journal of Audiology, 2012)
Objective: To study whether a change in cochlear tuning, measured using OAEs, could be detected due to contralateral activation of the efferent system using broadband noise. Design: Cochlear tuning measures based on SFOAE phase gradients and SFOAE-2TS 'Q' were used to test this hypothesis. SFOAE magnitude and phase gradient were measured using a pure-tone sweep from 1248 to 2496 Hz at 50 dB SPL. 2TS curves of SFOAE were recorded with a suppressor frequency swept from 1120 to 2080 Hz at 50 dB SPL. DPOAE f2-sweep phase gradient was also obtained to allow comparisons with the literature. All three assays were performed across with- and no-CAS conditions. Study sample: Twenty-two young, normal-hearing adults. Results: CAS did not produce a statistically significant change in the tuning metric in any of the OAE methods used, despite producing significant reductions in the OAE magnitude. Conclusion: It is unknown whether this insensitivity to CAS is due to an insensitivity of these three measures to cochlear mechanical tuning. The results suggest that any changes in tuning induced by CAS that may occur are small and difficult to detect using the OAE measurement paradigms used here.